AFRICAN STARS: STUDIES IN BLACK SOUTH AFRICAN PERFORMANCE, by Veit Erlmann, Chicago Studies in Ethnomusicology, edited by Philip V. Bohlman and Bruno Nettl.) Chicago and London: University of Chicago Press, 1991, xxi plus 214 pp., music examples, photos, bibliography, index. - Rycroft, David K. (International Library of African Music, 1996)
pages: 137-145
Keywords: South Africa; African Music